Short-term effects of fine and coarse particles on deaths in Hong Kong elderly population: An analysis of mortality displacement. (October 2018) - Qiu, Hong; Pun, Vivian C.; Tian, Linwei
Abstract: Background: While numerous studies worldwide have evaluated the short-term associations of fine and coarse particulate matter (PM) air pollution with mortality and morbidity, these studies may be susceptible to short-term harvesting effect. We aimed to investigate the short-term association between mortality and PM with aerodynamic diameter less than 2.5 μm (PM2.5 ) and those between 2.5 and 10 μm (PMc) within a month prior to death, and assess the mortality displacement by PM2.5 and PMc among elderly population in Hong Kong. Methods: We obtained air pollution data from January 2011 to December 2015 from Environmental Protection Department, and daily cause-specific mortality data from Census and Statistical Department of Hong Kong. We performed generalized additive distributed lag model to examine the acute, delayed and long-lasting effects of PM2.5 and PMc within one month on mortality. Results: We observed a statistically significant association of PM2.5 and PMc exposure over lags 0–6 days with all natural mortality and cardio-respiratory mortality. The overall cumulative effect of PM2.5 over 0–30 lag days was 3.44% (95% CI: 0.30–6.67%) increase in all natural mortality and 6.90% (95% CI: 0.58–13.61%) increase of circulatory mortality, which suggested the absence of mortality displacement by PM2.5 . On the other hand, no significant cumulative association with mortality was found for PMc over 0–30 lag exposure window, and thus mortality displacement by PMc cannot be ruled out. Findings remained robust in various sensitivity analyses. Conclusions: We found adverse effect of both PM2.5 and PMc exposure within one week prior to death. While there was no evidence of mortality displacement in the association of PM2.5 exposure over one month prior with all natural and circulatory mortality, mortality displacement by PMc cannot be ruled out. PM2.5 may contribute more to the longer term effect of particulate matter than PMc. Graphical abstract: Highlights: No studies have assessed the mortality displacement by fine (PM2.5 ) and coarse PM (PMc) in the same setting. We performed generalized additive distributed lag model to examine the mortality displacement. We observed acute effects of both PM2.5 and PMc on mortality within one week prior to death. We found no evidence of mortality displacement in the association of PM2.5 exposure within one month. We could not rule out the mortality displacement by PMc. Abstract : This time series study with analysis of mortality displacement demonstrated the acute effects of both fine and coarse PM on mortality within one week and no evidence of mortality displacement by PM2.5 within one month prior to death.